INCOME SMOOTHING ANALYSIS ON SECURITY COMPANY - Rika Desiyanti; Robi Hendra Desaputra (Jurnal Apresiasi Ekonomi, 2018)
This study  examine about income smoothing in subsector security company of finance companies at Indonesia Stock Exchange. Also examine the influence of company size, financial leverage and net profit margin to income smoothing. Eckel index and multiple regession is used to determine the income smoothing practice. Population of this research are security company are listed in the Indonesia Stock Exchange in 2010-2014. Samples were determined by the census methods, with 9 companies.  The hypothesis use fixed effect model (FEM)and multiple regression to examine the influence of size of the company, financial leverage and net profit margin to income smoothing practice with using Eviews 8.The result of this study showed that financial leverage affects significantly to income smoothing. Size of company and net profit margin does not affect significantly to to income smoothing. Keywords : Size Of The Company, Financial Leverage, Net Profit Margin, And Income Smoothing.